(untitled) (MAUSAM, 1970)
This report discusses the development and structure of the Arabian Sea cyclone of20-29 May 1963. The structure is discussed on the basis of special reconnaissance flights carried out by research aircraft of the U. S. Weather Bureau- Research Flight Facility. Analyses of surface, 500-mb and 200-mb flow are used to illustrate the conditions associated with cyclone development and motion. They give, in addition, a good view of the circulation patterns during the transition from the pre-monsoon to the summer monsoon regime northern Indian Ocean. The factors that seem to have influenced the development of this cyclone and the structure of the system during its life cycle were found to be quitesimilar to those in hurricanes in the Atlantic Ocean.